2021
DOI: 10.1007/s12098-021-03783-9
|View full text |Cite
|
Sign up to set email alerts
|

Wickerhamomyces anomalus: A Rare Fungal Sepsis in Neonates

Abstract: To the Editor: Recently, we came across two cases of rare invasive fungal sepsis in our neonatal unit caused by Wickerhamomyces anomalus (WA).The first case was an outborn full-term 2.2 kg female neonate, referred to us on day 4 of life with worsening respiratory distress since 2 h after delivery. The neonate required mechanical ventilation (MV) with other supportive management. Blood culture through BACTEC system grew fungal colonies on Sabouraud agar. Matrix-assisted laser desorption ionizationtime of flight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…A total of 243 articles from PubMed and Scopus were screened. Finally, 36 met the present study’s inclusion criteria [ 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. These 36 studies involved 170 patients in total.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 243 articles from PubMed and Scopus were screened. Finally, 36 met the present study’s inclusion criteria [ 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. These 36 studies involved 170 patients in total.…”
Section: Resultsmentioning
confidence: 99%
“…Given the rarity of fungemia by this pathogen, its epidemiology and clinical characteristics have not been adequately described. Indeed, only scarce case reports with literature reviews or small series can be found in the literature [ 28 , 29 ]. The present review aimed to provide data on the epidemiology, antifungal resistance, clinical characteristics, treatment, and outcomes of fungemia by W. anomalus by extracting all the available information from published original reports in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies employed traditional biochemical tests for species identification, but no molecular confirmation. Shubham et al (2021) reported two cases of nosocomial blood infection with W. anomalus in a neonatal unit in India. Both patients required mechanical ventilation and other supportive measures.…”
Section: Wickerhamomyces Anomalusmentioning
confidence: 99%
“…Seven publications reported potential safety concerns. Several studies reported opportunistic infections with W. anomalus in humans or neonate children with various predisposing conditions but could not be evaluated appropriately due to uncertainties or problems with the methodology used for identification of yeasts (Alp et al, 2021;Shubham et al, 2021;Zhang et al, 2021). Desnos-Ollivier et al (2021) reported antimycotic susceptibility of 36 strains of W. anomalus in a retrospective study of more than 9.000 clinical strains.…”
Section: Wickerhamomyces Anomalusmentioning
confidence: 99%